Role of Aromatic Interactions in Temperature-Sensitive Amphiphilic Supramolecular Assemblies - Munkhbat, Oyuntuya (Langmuir : the ACS journal of surfaces and colloids, 2016)
Aromatic interactions were found to greatly influence the temperature-dependent dynamic behavior within supramolecular assemblies. Using an amphiphilic dendron, we systematically changed the hydrophobic groups introducing increasing levels of aromaticity while keeping the hydrophilic part constant. We show that the supramolecular assemblies become less sensitive to temperature changes when aromatic interactions in the aggregate are increased. Conversely, the absence of aromaticity in the hydrophobic moieties produces temperature-sensitive aggregates. These results show that subtle molecular-level interactions can be utilized to control temperature-sensitive behavior in the nanoscale. These findings open up new design strategies to rationally tune the behavior of stimuli-responsive supramolecular assemblies on multiple spatiotemporal scales